A new species of Nannosquilla (Stomatopoda: Nannosquillidae) from the Western Atlantic Ocean - de Albuquerque, Débora Lucatelli; Coelho, Petrônio Alves (Zootaxa, 2009)
The family Nannosquillidae contains thirteen genera, one of which is Nannosquilla, composed of twenty-five species. The genus is distributed on both sides of the American continent, but contains no amphi-American species, and only one species in Indonesia. During surveys conducted in the Potiguar Basin, Rio Grande do Norte state/BR, a new species, Nannosquilla potiguara, was found. The new species is similar to N. schmitti, sharing the characters of seven intermediary fixed teeth in the posterior margin of telson on both side of the submedians movable tooth, and the inner spine on the uropodal protopod being longer than the outer. The two species differ in the number of teeth of the raptorial claw, in the morphology of rostral plate, and in the median projection of telson. From the Brazilian coast only one other species, N. dacostai, has previously been recorded. It is similar to new species in the subpentagonal rostral plate and the inner spine of uropodal protopod being longest, but N. potiguara n. sp. differ by a larger number of teeth on the dactylus of the raptorial claw and by fixed teeth on each side of the submedian movable teeth at telson. A key to the Atlantic species of Nannosquilla is given.